2012
DOI: 10.1039/c2cc37261d
|View full text |Cite
|
Sign up to set email alerts
|

A mechanochemically synthesised solid solution enables engineering of the sorption properties of a Werner clathrate

Abstract: Mechanochemical synthesis has been used to obtain two Werner complexes and their solid solution that could not be obtained by conventional "wet" chemistry; remarkably, despite the structural and chemical similarity, the solid solution exhibits sorption properties that differ from those of the pure compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Indeed many solid solutions of non‐isostructural crystals are known; they show limited solubility 8b. 9a, 23…”
Section: Discussionmentioning
confidence: 99%
“…Indeed many solid solutions of non‐isostructural crystals are known; they show limited solubility 8b. 9a, 23…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been renewed interest in Werner clathrates 5,6 and Lusi and Barbour 7 have described polymorphism associated with an order-disorder phase transition of the guest in the [Ni(NCS) 2 (4-phenylpyridine) 4 ] clathrate dependent on the thermal range investigated. The host preferentially discriminated in favour of one of the three isomers of xylene in solid-vapour competition experiments 8 and Batisai and co-workers 9 explored the preparation of phases by mechanochemical techniques which resulted in a series of solid solutions. Different sorption properties were exhibited by these solid solutions compared with the pure Werner complexes.…”
Section: Introductionmentioning
confidence: 99%
“…While investigating the separation properties of a Werner complex [17][18][19] we found that one of its clathrates undergoes a single-crystal to single-crystal transformation in which the crystal symmetry is increased while the unit cell metrics are preserved. The transformation is associated with an orderdisorder phase transition involving the guest.…”
mentioning
confidence: 99%
“…Remarkably, despite their structural similarity, the same behaviour was not observed in other clathrates of the same host. [17][18][19] Crystals of [Ni(NCS) 2 ppp 4 ]•2m-xyl (1) (ppp = para-phenylpyridine, m-xyl = meta-xylene) were obtained following a previously reported procedure. A single crystal was selected and its crystal structure determined with the diffraction data collected at 100 K (1 100 ).…”
mentioning
confidence: 99%